Monotonicity and Symmetry of Solutions to Fractional Laplacian in Strips - Tao Sun (Hindawi Limited, 2021)
In this paper, using the method of moving planes, we study the monotonicity in some directions and symmetry of the Dirichlet problem involving the fractional Laplacian −Δα/2ux=fux,x∈Ω,ux>0,x∈Ω,ux=0,x∈ℝn\Ω, in a slab-like domain Ω=ℝn−1×0,h⊂ℝn.